Accumulation rates, coarse fraction and carbonate abundances at DSDP Hole 82-558A - Gordon G Start (PANGAEA, 1985)
Carbonate and coarse fraction data from Hole 558A record variations in the carbonate system for the Pleistocene. The late Pleistocene carbonate record from Hole 558A can be correlated to Atlantic carbonate records with similar accumulation rates. The correlation between carbonate and coarse fraction record in Hole 558A does not remain constant. The early Pleistocene carbonate-coarse fraction correlation is opposite of the typical North Atlantic pattern, whereas late Pleistocene carbonate-coarse fraction correlation does not show consistent pattern. The different relationships between the carbonate and coarse fraction records suggests that the carbonate system in the North Atlantic changed between the early and late Pleistocene.
Supplement to: Start, GG (1985): Carbonate and coarse fraction records of the Pleistocene interval in the North Atlantic, hydraulic piston corer Hole 558A. In: Bougault, H; Cande, SC; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 82, 629-635, https://doi.org/10.2973/dsdp.proc.82.138.1985